IMPLEMENTASI SIPADES UNTUK PENINGKATAN TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN ASET DI DESA ILOHELUMA - Ade Mohamad; Dharmawaty S. Makur (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze the implementation of SIPADES in improving transparency and accountability of asset management in Iloheluma Village. The method used is descriptive qualitative through observation, in-depth interviews, and documentation. The results of the study indicate that the implementation of SIPADES version 01 is still offline-based and not optimal. The main obstacle lies in the lack of understanding of village operators due to minimal technical guidance, which is caused by budget constraints from the central government. Other obstacles include the lack of conformity of communication indicators, human resources, disposition, and bureaucratic structures with applicable standard operating procedures. The use of manual methods in reporting also slows down the process of digitizing asset management. The development plan to version 02 of SIPADES in Gorontalo Regency is also constrained by budget problems. Keywords: SIPADES, Transparency, Accountability, Village Asset Management, Information System